Regulation of tryptophan-2,3-dioxygenase and pineal indoleamines by selected tryptophan derivatives and antidepressants - Walsh, Harold Archibold (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1997)
The regulation of tryptophan-2,3-dioxygenase (TDO) (EC 1.13.1.12) and, to a lesser extent, pineal indoleamines, both in vitro and in vivo, is examined in this study. Rat liver TDO is a cytosolic enzyme which plays a crucial role in the regulation of circulating tryptophan (TRP) levels. Stimulation of this enzyme by heme enhances the catabolism of TRP, making less TRP available for uptake into the brain and other tissues, and for protein synthesis. At pH 7, the enzyme has an approximate Km of 100Î¼M, is subject to substrate inhibition immediately beyond Sopt([S] at Vmax), and response of the enzyme is cooperative in both uninhibited and inhibited regions. Hill analysis of the uninhibited region reveals a biphasic plot and two classes of binding sites. Negative cooperativity is brought about through deprotonation of the enzyme. Substrate iphibition also occurs at both acidic and basic pH values with concomitant shifts in Sopt. The results obtained indicate that substrate inhibition could be an additional mechanism whereby the flux through the TRP-kynurenine pathway is regulated. TDO is subject to a diurnal rhythm, with peak activity during the pre-dark period and the loweSt activity towards the end of the dark period. It is possible that the enzyme controls the synthesis of the neurotransmitter serotonin (5-HT), and that the circadian rhythm in TDO activity is due to the endogenous rhythm of melatonin (aMT) production by the pineal gland. In the present study, aMT displaces TRP from bovine serum albumin (BSA) in vitro, and it is therefore possible for the indoleamine to regulate the availability of TRP for uptake into the brain for conversion to its derivatives. Chronic intraperitoneal administration of aMT affects physiological hepatic parameters in rats, such as TDO activity and stromal fatty acid composition, whilst no observable effect is demonstrable with respect to protein synthesis, nucleic acid metabolism, membrane fatty acid composition and pineal indole biosynthesis. On the other hand, chronic treatment of rats with antidepressants, the tricyclic desmethylimipramine (DMI) and the selective serotonin reuptake inhibitor (SSRI), fluoxetine, reveals significant negative alterations in TDO concentrations and pineal indole amine synthesis. Combining aMT with any of these two drugs normalises the activity of the hepatic enzyme. DMI is found to be an effective inhibitor of TDO in the micromolar range in vitro, and also affects total enzyme concentrations in vivo. Fluoxetine has no effect on TDO in vitro, but in vivo also reduces total enzyme levels in the liver. However, the SSRI does not affect conjugation between apo- and holoenzyme. Instead, it decreases extant holoenzyme levels. Indoleamine synthesis by the pineal gland, in organ culture, is altered by both antidepressants, although in different ways. DMI increases N-acetylserotonin levels and reduces the output of methoxyindole acetic acid and meth6xytryptophol. Fluoxetine treatment markedly reduces aMT concentrations and also brings about high levels of the 5-HT catabolites, 5-hydroxytryptophol and 5-hydroxyindole acetic acid. Insulin also lowers aMT synthesis significantly in pineal organ cultures, via a mechamsm that involves inhibition of the enzyme, N-acetyl transferase, that regulates aMT synthesis. The effects of insulin on pineal indole metabolism are due to the observation that a carbohydrate rich diet which induces insulin release elevates plasma TRP and brain 5-HT, but has no effect on pineal TRP and indole amine synthesis. It could thus be possible for insulin to have an effect on the pineal, since the latter is outside the blood brain barrier. The finilings of this study support the biogenic amine deficiency hypothesis, implicating some of the major biogenic amines such as noradrenaline (NA), 5-HT and aMT in depression. There is believed to be a deficiency of NA and 5-HT at their respective synapses in the depressed state. The drug DMI could act, firstly, by inhibiting TDO and thus increasing plasma TRP levels, and could, secondly, stimulate NA release and inhibit NA reuptake at the pineal membrane. The combined effect would be to enhance aMT synthesis, with eventual remission. Fluoxetine, on the other hand, appears to utilize a slightly different mode of action to DMI, which seems to focus on the preservation of 5-HT. The fact that aMT counteracts the effects of both antidepressants, and restores the activity of TDO to that of the controls, is also consistent with the observation that the therapeutic action of drugs such as these coincides willi the restoration of normal plasma levels of the neurohormone in depressives. In view of the biogenic amine deficiency hypothesis of depression and the contentious claim that TDO is the major peripheral determinant of brain TRP, brain 5-HT and ultimately aMT, the regulation of TDO is investigated and discussed. The study concludes that TDO activity is regulated by a number of endogenous compounds which are mainly derivatives of TRP, such as aMT and oxidized nicotinamide adenine dinucleotide and exogenous substances, of which DMI and fluoxetine are but two. In addition, modulation of IDO activity in depression appears to be an important aspect of antidepressant action. aMT, the product of the pineal gland, also has the potential to increase plasma TRP and hence forebrain TRP levels, and ultimately 5-HT concentrations, firstly by displacing TRP from serum albumin and secondly by inhibiting TDO.
Keywords: Antidepressants; Tryptophan -- Physiological effect; Tryptophan -- Therapeutic use; Depression, Mental -- Treatment